2017
DOI: 10.1182/bloodadvances.2017012732
|View full text |Cite|
|
Sign up to set email alerts
|

Changes in bone marrow innate lymphoid cell subsets in monoclonal gammopathy: target for IMiD therapy

Abstract: Key Points Altered number, subset composition, and function of bone marrow innate lymphoid cells are early events in monoclonal gammopathies. Pomalidomide therapy leads to reduction in Ikzf1 and Ikzf3 and enhanced human innate lymphoid cell function in vivo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
31
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 25 publications
(24 reference statements)
2
31
0
Order By: Relevance
“…Therefore, alterations in innate lymphocytes appear to be an early feature in the evolution of gammopathies, which is consistent with prior studies (5,30). Recent studies suggest that innate cells may be targets for immunomodulatory drugs currently being explored for prevention of myeloma (5).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Therefore, alterations in innate lymphocytes appear to be an early feature in the evolution of gammopathies, which is consistent with prior studies (5,30). Recent studies suggest that innate cells may be targets for immunomodulatory drugs currently being explored for prevention of myeloma (5).…”
Section: Discussionsupporting
confidence: 87%
“…Tumor cells in MGUS carry the great majority of genomic alterations, including the mutational burden found in MM (2). Prior studies have demonstrated the capacity of T cells to mediate specific recognition of MGUS cells (3,4); recent data also show alterations in innate lymphoid cells in these lesions (5). Antitumor T cells are often enriched in the bone marrow of MM patients (6, 7); therapeutic adoptive transfer of bone marrow T cells is being explored in MM (8).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies demonstrated how lenalidomide binds the CRBN–CRL4 E3 ubiquitin ligase , increasing ubiquitination and decreasing protein levels of two of the Ikaros family members, Ikaros and Aiolos, with high specificity . A drug with similar properties to lenalidomide was recently used in a cohort of patients affected by multiple myeloma, showing IKZF3 and IKZF1 downregulation in circulating ILCs . We showed here that lenalidomide‐mediated suppression of Aiolos and Ikaros expression affect ILC3−ILC1/NK cell balance, inhibiting ILC1/NK cell differentiation while maintaining ILC3 function.…”
Section: Discussionmentioning
confidence: 57%
“…ILCs are a new subset of innate immune cells known to be involved in the regulation of immunity, inflammation and tissue homeostasis ( 109 ). The study also reported that ILCs are increased in BM of MGUS patients compared to HDs and their functions are enhanced in MGUS but decline in patients with asymptomatic MM ( 108 ). These results thus provided evidence that ILCs are among the earliest cell subsets enriched in the tumor microenvironment during the evolution of monoclonal gammopathies and represent a possible target to prevent disease progression by acting on their IKZF1 expression.…”
Section: Immunologic Effects Of Imids- Releasing the Ikaros Checkpoinmentioning
confidence: 88%
“…More recently, a study from Bailur et al ( 108 ) reported that Pom also reduces IKZF1 and IKZF3 levels on innate lymphoid cells (ILCs) and enhances their function, as demonstrated by the increased IFN-γ production both in vitro and in vivo ( 108 ). ILCs are a new subset of innate immune cells known to be involved in the regulation of immunity, inflammation and tissue homeostasis ( 109 ).…”
Section: Immunologic Effects Of Imids- Releasing the Ikaros Checkpoinmentioning
confidence: 99%